European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on European Securities and Markets Authority. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This article reviews the European Securities and Markets Authority (ESMA) of the European Union. ESMA performed a role in the regulation and supervision of the securities market. ESMA was created to supervise the financial system to enhance financial markets. In crisis management, ESMA focused on coordination, and identified and monitored risks. It also played an important role in the single rule book credit rating agency supervision. The assessment of the ESMA in the European Union is a next level in economic development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet